The impact of open access journals on library and information scientists' research in Taiwan / Mei-Ling Wang - Wang, Mei-Ling (2011)
As some library and information science (LIS) journals in Taiwan are open access, the aim of the study is to investigate what, if any, impact open access journals have on library and information science scholars‘ research in Taiwan. Therefore, the objectives of the study is to explore the scholarly productivity of LIS scholars in Taiwan, to find out what articles they publish and OA articles as a percentage of all titles, and to calculate the mean citation rate of open access articles and articles not freely available online. A bibliometric method was used in the study. To determine whether a difference in research impact existed, two research impact indicators were used, that is, open access articles as a percentage of all published titles and mean citation rate of open access articles and those not freely available online. Data on published articles with citation counts by the LIS scholars in Taiwan from 2000 to 2009 was collected from the ACI Database and Social Science Citation Index Database. The study shows that for 72 LIS scholars who were subjects of the investigation, 64 of them had published 745 articles within the previous ten years: 679 articles in Chinese and 66 articles in English; 499 of these were OA articles, and 264 were non-OA articles; OA articles constituted 66.98% of the total number of academic articles. The mean citation rate of OA versus non-OA article citation was 1.29.Analysis of impact indicators shows that open access journals have an impact on the research of LIS scholars in Taiwan, in particular, LIS OA journals have more research impact in Chinese than those in English.